Determinants of Net Interest Margin on Conventional Banking: Evidence in Indonesia Stock Exchange - Lestari, Henny Setyo; Chintia, Helda; Akbar, Ilham Cahyo (University of Merdeka Malang, 2021)
Net Interest Margin (NIM) is an important indicator in assessing the sustainability and health of the banking system. A bank that has a high NIM means that the bank has a greater opportunity to generate profits, power to resist the financial crisis, and provide welfare for parties who have an interest in the bank. This study aims to determine the factors that influence NIM. The sample used in this study is the banking industry listed on the Indonesia Stock Exchange (BEI) from 2015 to 2019. In this study the independent variables used are bank size, lending scale, credit risk, equity capital, loan to deposit ratio, management efficiency and inflation rate. The dependent variable in this study is NIM. The number of samples used was 37 conventional banks which were taken using purposive sampling method. By using multiple regression analysis with the General Least Square (GLS) approach method. The results of this study indicate that the bank size, credit risk, equity capital, loan to deposit ratio, management efficiency and inflation rate have an effect on NIM, while the lending scale has no effect on NIM. The results of this study are expected to be used by future researchers, bank managers, and investors in determining the factors that can affect the NIM at the Bank.DOI: https://doi.org/10.26905/jkdp.v25i1.5102